ANALYSIS OF THE EXCHANGE RATE LEVEL OF EMERGING MARKET COUNTRIES DURING THE COVID-19 OUTBREAK - Fredo, Ramiandrisoa; Heriqbaldi, Unggul (LPPM STIE Muhammadiah Bandung, 2024)
This study investigates the influences of the COVID-19 Pandemic on exchange rate level in two emerging countries, India and Indonesia, using ARDL Model with time series data from 2020 to 2022. The research examines how the exchange rate level of these two countries changed during the pandemic, and how the factors affected their sovereign bond yields and capital flows. Furthermore, this study compares and contrasts the exchange rate performance of these two countries with different macroeconomic vulnerabilities, such as Interest Rate Differential, Inflation Rate Differential, Industrial Production Index, and Stock Market. The findings reveal that the interest rate differential is the most significant factor influencing exchange rates for both countries in the short run and long run, while the inflation rate differential and the industrial production index are also important for Indonesia. Overall, these two countries should adopt monetary and fiscal policies that maintain a competitive interest rate level, control the inflation rate, stimulate the industrial production, and enhance the transparency and the efficiency of their stock markets. This paper provides policy implications and recommendations for financial stability in the post-pandemic.